Assessment of Environmental Pollution using Electrical Resistivity and Logging Techniques over A Municipal Dumpsite of Ijagun Ijebu Ode - Adebisi, N. O.; Bayewu, O. O.; Ariyo, S. O.; Mosuro, G. O.; Oloruntola, O. M.; Alaka, A. O.; Odugbesan, O. O. (Iraqi Journal of Science, 2022)
The present study aims to assess environmental pollution using the resistivity method and geological logging technique over a municipal dumpsite of Ijagun Ijebu Ode, underlain by the Afowo Formation within the Dahomey Basin southwestern Nigeria. Forty vertical electrical resistivity soundings stations and six 2D electrical resistivity imaging profiles using Schlumberger and Wenner array respectively with maximum spread-length of 40m at each sounding and profile length of 60 m and 120 m and one borehole log were carried out. Three geoelectrical layers were obtained in the control area, their resistivity values with their corresponding depth of sediment materials is 126 Ωm – 724 Ωm at depth range 0.9 m – 1.1 m (topsoil), 608 Ωm – 2517 Ωm at depth range 3.5 m – 17.7 m (sandy layer), and 800 Ωm – 6046 Ωm (dry sandy layer). Along with the 2D resistivity imaging profiles over the control (1 and 2), four geo-electric layers characterized by Resistivity values range of 40 Ωm – 126 Ωm (loam), 135 Ωm – 418 Ωm (loamy sand), 500 Ωm – 1500 Ωm (sandy), and >3000 Ωm (dry sand) were revealed. The lithology recovery from the logging techniques shows the subsurface is underlined chiefly with sand, which shows a significant correlation with the geophysical method. The lower values of resistivity at the dumpsite are clear evidence of the subsurface contamination of the sandy layer. The 2D images revealed the contaminated zone thickness ranges from 2 m in the northwest to 25 m in the southeastern part. The protective capacity map derived from the VES showed that the dumpsite is underlain by poorly protected sandy lithology, prone to leachate infiltration. Relocation of the dumpsite to a better protected environment or underlining the present area with an impermeable geotextile layer would halt further leachate invasion into the subsurface.